Utility of 18F-Fluorodeoxyglucose Positron Emission Tomography in Inflammatory Rheumatism, Particularly Polymyalgia Rheumatica: A Retrospective Study of 222 PET/CT - Amat, Julie; Chanchou, Marion; Olagne, Louis; Descamps, Lucie; Flaus, Anthime; Bouvet, Clément; Barres, Bertrand; Valla, Clemence; Molnar, Ioana; Cougoul, Arnaud; Mathieu, Sylvain; Aumaitre, Olivier; et al. (Frontiers in Medicine, 2020)
Purpose: The objective of this study was to evaluate periarticular FDG uptake scores from 18F-FDG-PET/CT to identify polymyalgia rheumatica (PMR) within a population presenting rheumatic diseases. Methods: A French retrospective study from 2011 to 2015 was conducted. Patients who underwent 18F-FDG-PET/CT for diagnosis or follow-up of a rheumatism or an unexplained biological inflammatory syndrome were included. Clinical data and final diagnosis were reviewed. Seventeen periarticular sites were sorted by a visual reading enabling us to calculate two scores: mean FDG visual uptake score, number of sites with significant uptake same or higher than liver uptake intensity and by a semi-quantitative analysis using mean maximum standardized uptake value (SUVmax). Optimal cut-offs of visual score and SUVmax to diagnose PMR were determined using receiver operating characteristics curves. Results: Among 222 18F-FDG PET/CT selected for 215 patients, 161 18F-FDG PET/CT were performed in patients who presented inflammatory rheumatism as a final diagnosis (of whom 57 PMR). The presence of at least three sites with significant uptake identified PMR with a sensitivity of 86% and specificity of 85.5% (AUC 0.872, CI-95% [0.81-0.93]). The mean FDG visual score cut-off to diagnose a PMR was 0.765 with a sensitivity of 82.5% and specificity of 75.8% (AUC 0.854; CI-95% [0.80-0.91]). The mean SUVmax cut-off to diagnose PMR was 2.168 with a sensitivity of 77.2 % and specificity of 77.6 % (AUC 0.842; CI-95% [0.79-0.89]). Conclusions: This study suggest that 18F-FDG PET/CT had good performances to identify polymyalgia rheumatic within a population presenting rheumatic diseases.